1995
DOI: 10.1111/j.1751-0813.1995.tb15032.x
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the indirect transmission of virulent ovine footrot in sheep yards and its spread in sheep on unimproved pasture

Abstract: Virulent ovine footrot was transmitted accidentally to a group of 23 adult Merino sheep (flock B) after holding for 1 hour in sheep yards, which earlier the same day had contained another flock (flock A) with < 1% prevalence of sheep with footrot lesions. Sheep in flock B were rendered susceptible to virulent footrot by grazing 600 mm high unimproved pasture dominated by paspalum (Paspalum dilatatum) and kangaroo grass (Themeda australis) during warm, humid and wet weather. In addition to moisture, interdigita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
5

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 12 publications
2
14
1
5
Order By: Relevance
“…The environment can also be a source for introduction of footrot as reported by Whittington et al [15] where a flock became infected after using the same yard used by an infected flock some hours earlier. The risk of introduction or re-introduction of footrot into a flock can be reduced by some principal preventive strategies as described by Abbott and Lewis [16]: animals should only be purchased from footrot-free flocks, purchased animals should be quarantined, or the flock should be sequestered from outside introduction.…”
Section: Discussionmentioning
confidence: 99%
“…The environment can also be a source for introduction of footrot as reported by Whittington et al [15] where a flock became infected after using the same yard used by an infected flock some hours earlier. The risk of introduction or re-introduction of footrot into a flock can be reduced by some principal preventive strategies as described by Abbott and Lewis [16]: animals should only be purchased from footrot-free flocks, purchased animals should be quarantined, or the flock should be sequestered from outside introduction.…”
Section: Discussionmentioning
confidence: 99%
“…D. nodosus has been isolated from clinically normal cattle [20], but cattle is not considered a source of virulent D. nodosus in sheep [10]. Indirect transmission of D. nodosus between sheep on unimproved pasture, which has resulted in virulent ovine footrot, has been reported [21]. Early studies by Egerton & Parsonson indicated that experimental transmission of D. nodosus from cattle to sheep can result in ovine footrot [22].…”
Section: Discussionmentioning
confidence: 99%
“…A significant relation was found between the hygiene and management practice categories and disease prevalence (Table 2). Prevalence of footrot depends on the environmental condition and pasture (Reilly et al, 2012;Whittington, 1995). The prevalence is higher in temperate climate with high temperature (Hussain et al, 2013).…”
Section: Resultsmentioning
confidence: 99%